KONSERVASI POHON GERONGGANG (Cratoxylum arborescens (Vahl.) Blume) OLEH MASYARAKAT LOKAL DALAM MENDUKUNG RESTORASI LAHAN GAMBUT DI KABUPATEN BENGKALIS RIAU - Putri Selaras; Elfis Elfis; Prima Wahyu Titisari (Gunung Djati Conference Series, 2023)
Bengkalis District is one of largest peatlands in Riau. However, peatlands in Bengkalis have been degraded by 57% due to careless logging plantations, so there is rapid subsidence, land draying, and more flammability. One of method to recover the peatland is by utilizing local plant such as geronggang tree (Cratoxylum arborescens (Vahl.) Blume). The benefit of ecological aspect from Geronggang trees was to maintaining peatland moisture, storage a lot of water and the same as many benefits for Bengkalis' citizen. This study aimed to provide information regarding the conservation of geronggang trees by local Bengkalis' people support the restoration of peatland. Primary and secondary data collected by observation and interview to local citizen. The results show that the Bengkalis cityzen has its own way for conserving geronggang trees, it is geronggang seeds are planted with mixed cropping system and the harvesting with thinning cutting system, cutting hallway (track) system, and cutting the embroidery. This is done for the sustainability of peat moisture on one side and maintaining of geronggang trees. Its means, the conservation efforts made by the local people of Bengkalis can maintain the existence of geronggang trees in the region and can help restoration of the degraded peatland.